Balanço de energia e sustentabilidade no perímetro irrigado Califórnia SE mediante imagens orbitais - Sabino, Fabiana Gonçalves (2008)
The main objective of the present work went evaluate the components of the swinging of energy and the evapotranspiração in semi-arid area using the algorithm SEBAL - Surface Energy Balances Algorithm it goes Land (Bastiaanssen, 1995) and images of the satellite Landsat-5 TM. The study area was the Irrigated Perimeter California located in the municipal district of Canindé of São Francisco - SE, Brazil. For attainment of the objectives images obtained in April 8, 2005 and December 7, 2006 were used, that they collect the irrigated areas of the perimeter, it leaves of the river San Francisco and areas with native vegetation. Was the albedo of the surface certain (?), vegetation indexes (NDVI, SAVI and IAF) and the temperature of the surface (Ts) for each pixel. The incident radiation of wave tans it was esteemed in function of the solar constant, of the atmospheric transmissividade, of the angle solar zenital and of the square of the distance relative Earth-sun. The incident radiation of long wave had as base for its estimate the temperature of the air measure in the meteorological station of surface and the emitted radiation of long wave esteemed with base in the surface temperature. Starting from those variables the radiation balance was determined (Rn) whose medium values esteemed by Landsat 5-TM for the 08/04/2005 were 565,0 W m- 2 and for the image of the 07/12/2006, 585,3 W m- 2. The flow of heat in the soil (G), esteemed in function of Rn, Ts? and of NDVI, it presented for the 08/04/2005 the medium value of 78,9 W m- 2, however, for the date of 07/12/2006 the medium value of that same variable was 79,1 W m- 2. The flow of sensitive heat (H), esteemed with the application of the process interativo, in function of the speed of the wind and of the medium height of the obtained of the meteorological station of surface vegetation and also with base in two reference pixels (hot and cold) to determine the temperature difference between the surface and the close air the same, did it present for the 08/04/2005 the medium value of 115W m-2. In 07/12/2006 the medium value of H esteemed by the referred satellite was 140,7 W m- 2. The flow of latent heat (?E), calculated as residual part of the swinging of energy to the surface, it presented medium values of 402,0 W m- 2 for the date of 08/04/2005 and of 365,5 W m- 2 for the 07/12/2006. The evapotranspiration (ET) it presented medium value of 3,5 mm day- 1 for the 08/04/2005 with maximum value of 5,8 mm day- 1. Already for 07/12/2006 dear medium ET was of 3,2 mm day- 1, with a maximum value of 5,9 mm day- 1.